2023
DOI: 10.3390/liquids3030023
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of C70 Fullerene in a Binary Mixture of Xylene and Tetrahydrofuran

Urol K. Makhmanov,
Shaxboz A. Esanov,
Dostonbek T. Sidigaliyev
et al.

Abstract: The self-organization properties of C70 fullerene molecules in a xylene/tetrahydrofuran binary mixture were studied for the first time by optical absorption, refractometry, and dynamic light scattering. A correlation has been established between the change in the refractive index of the C70/xylene/tetrahydrofuran solution and the degree of self-organization of C70 molecules in the medium at various concentrations and storage periods of the solution. It is shown that the features of the optical absorption spect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…A series of studies with C 60 and C 70 fullerenes were performed by Makhmanov et al [113][114][115][116]. Two methods of preparation of C 60 in toluene, non-equilibrium and equilibrium, were compared [113].…”
Section: Forced Aggregation Of Fullerenes In "Good" Solventsmentioning
confidence: 99%
See 1 more Smart Citation
“…A series of studies with C 60 and C 70 fullerenes were performed by Makhmanov et al [113][114][115][116]. Two methods of preparation of C 60 in toluene, non-equilibrium and equilibrium, were compared [113].…”
Section: Forced Aggregation Of Fullerenes In "Good" Solventsmentioning
confidence: 99%
“…Storing C 60 in toluene for the same period results in the formation of particles with size ≤50 nm, as determined by the TEM and AFM methods. It was revealed that in C 70 solutions in xylene-tetrahydrofurane, the changes of the refractive index over time reflect the formation and stabilization of colloidal particles [116].…”
Section: Forced Aggregation Of Fullerenes In "Good" Solventsmentioning
confidence: 99%